2012
DOI: 10.4049/jimmunol.1200580
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Present Antigen in the Context of MHC Class I

Abstract: Platelets are most recognized for their vital role as the cellular mediator of thrombosis, but platelets also have important immune functions. Platelets initiate and sustain vascular inflammation in many disease conditions, including arthritis, atherosclerosis, transplant rejection, and severe malaria. We now demonstrate that platelets express T cell costimulatory molecules, process and present Ag in MHC class I, and directly activate naive T cells in a platelet MHC class I-dependent manner. Using an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
174
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 59 publications
(55 reference statements)
2
174
0
4
Order By: Relevance
“…It now appears that, in syngeneic systems, activated platelets can express nascent MHC class I molecules, and these have the ability to present Ags to CD8 + T cells. Chapman et al (76) elegantly demonstrated that activated platelets can present malarial peptides to malaria-specific T cells, and this leads to an enhanced immunity against the parasite. Thus, depending on the source of MHC (surface bound or internalized), platelets can mediate either T cell suppression or activation.…”
Section: Platelet Mhc Class Imentioning
confidence: 99%
“…It now appears that, in syngeneic systems, activated platelets can express nascent MHC class I molecules, and these have the ability to present Ags to CD8 + T cells. Chapman et al (76) elegantly demonstrated that activated platelets can present malarial peptides to malaria-specific T cells, and this leads to an enhanced immunity against the parasite. Thus, depending on the source of MHC (surface bound or internalized), platelets can mediate either T cell suppression or activation.…”
Section: Platelet Mhc Class Imentioning
confidence: 99%
“…Platelets are often called antigen presenting cells (APCs) as they activate T cells through pMHCI 78. The pMHCI is constitutively expressed by platelets and their expression increases significantly during inflammation 79…”
Section: Immune System and Its Complexitymentioning
confidence: 99%
“…We have also performed studies showing that CXCL4-/-mice have reduced mortality from CM [4]. Damage caused by CXCL4 progresses through T-Cell and monocyte activation and migration resulting into BBB breakdown [19][20][21], which in turn also results in increased permeability of cerebral micro-capillaries. Other groups have also demonstrated that T-Cell activation is an important step in CM progression [22].…”
Section: Platelet -Specific Cytokines and Cerebral Malariamentioning
confidence: 99%
“…We have demonstrated that the CXCL4 participates in the progression of CM. Also, CXCL4-mediated cerebral damage is accompanied by T-Cell and monocyte activation plus consequent BBB breakdown [18][19][20][21]. Both platelets and monocytes can release the cytokines upon the onset of CM.…”
Section: Platelet -Specific Cytokines and Cerebral Malariamentioning
confidence: 99%